2017
DOI: 10.1101/173112
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel pleiotropic risk loci for melanoma and nevus density implicate multiple biological pathways

Abstract: The total number of acquired melanocytic nevi on the skin is strongly correlated with melanoma risk. Here we report a meta-analysis of 11 nevus GWAS from Australia, Netherlands, United Kingdom, and United States, comprising a total of 52,506 phenotyped individuals. We confirm known loci including MTAP, PLA2G6, and IRF4, and detect novel SNPs at a genome-wide level of significance in KITLG, DOCK8, and a broad region of 9q32. In a bivariate analysis combining the nevus results with those from a recent melanoma G… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 37 publications
(96 citation statements)
references
References 95 publications
(40 reference statements)
5
91
0
Order By: Relevance
“…We hypothesise that we were not able to replicate the association with IRF4 because the effect of these variants on the H&N plus trunk and the lower limbs, which include 26% and 31% of the total naevus count, has an opposite direction, therefore nullifying the effect on the whole body. On the other hand, it is likely that DOCK8 and KITLG exert a small effect on naevus count, detectable only by a large sample, as that reached in the recent meta‐analysis study of 52,506 individuals that lead to their identification (Duffy et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We hypothesise that we were not able to replicate the association with IRF4 because the effect of these variants on the H&N plus trunk and the lower limbs, which include 26% and 31% of the total naevus count, has an opposite direction, therefore nullifying the effect on the whole body. On the other hand, it is likely that DOCK8 and KITLG exert a small effect on naevus count, detectable only by a large sample, as that reached in the recent meta‐analysis study of 52,506 individuals that lead to their identification (Duffy et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Genome‐wide association studies have shown that melanoma and naevus count share a common genetic background (Duffy et al, ). According to Whiteman's “divergent pathway hypothesis”, subjects with high melanocyte proliferation are more likely to develop melanoma at those body sites showing high naevus count (Whiteman et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study highlighted two genes, OCA2 and IRF4 , that were associated with iris colour and iris pigmented lesions. OCA2 does not have a large effect on skin freckling and naevus count, whereas IRF4 is a major gene for skin freckling and naevi and has a growth regulatory effect on cutaneous melanocytes . We found that other known melanocytic naevus genes, MTAP (rs7023329) and PLA2G6 (rs132972), are not associated with iris pigmented lesions .…”
Section: Discussionmentioning
confidence: 70%